Monaco : Assessment of the Supervision and Regulation of the Financial Sector Volume II--Detailed Assessment of Observance of Standards and Codes. (IMF Staff Country Reports; Country Report, 2003)
The detailed assessments of the Offshore Financial Center Assessment of Monaco reviews the assessments of the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) related principles of the Basel Core Principles for Effective Bank Supervision, of the AML/CFT regime based on the Bank/IMF Draft Methodology, and of securities regulation on the basis of the International Organization of Securities Commissions Objectives (IOSCO) and Principles of Securities Regulation.